Akuntabilitas Penetapan Sima Kerajaan Medang Masa Pemerintahan Dyah Balitung 898-910 M - Maharani Wuryantoro; Eko Ganis Sukoharsono; Aji Dedi Mulawarman (Universitas Muhammadiyah Malang, 2024)
Purpose: This paper aims to explore accounting and accountability in sima policies during the Medang Kingdom era. Methodology/approach: Accounting and accountability was viewed using Foucault's Power-Knowledge perspective Findings: Accountability during the Medang Kingdom was rooted in eight practices in the lives of leaders known as Astabrata. Sima's policy as a reflection of Astabrata is closely related to the functions of accounting, accountability and control. Evidence shows that accounting power is manifested in many ways, including determining the size of the sima, business limits, determining pasek-pasek, the rights and obligations of sima leaders regarding reporting, and recording on inscriptions and palm leaves. This paper argues that accounting plays a role in legitimizing power through knowledge that develops in society through these eight life practices Practical and Theoretical contribution/Originality: Accountability studies taken from the royal period are relatively rare, so that research can be carried out by using a knowledge of power perspective as a tool to reveal the accountability of sima policies Research Limitation: The limitations of the research lie in the data source, namely the research inscription may not be able to provide a complete picture of accounting and accountability practices at that time